Elevated blood lead levels and associated risk factors among school children in a non-industrialized city in Indonesia - Nurjannah Nurjannah; Noralina Noralina; Rina Suryani Oktari; Shr-Jie Wang (PLoS ONE, 2025)
Environmental lead exposure in children is a big public health problem in industrial cities in Indonesia. However, exposure to lead can take place in other settings. Our survey in Banda Aceh was the first in a non-industrial Indonesian city. This study was conducted with 130 randomly selected children between October and December 2022, by examining their blood lead samples and administering structured questionnaires on family demographics and environmental factors (i.e., water source and roof type). Following the Centers for Disease Control and Prevention (CDC) guidelines, an elevated blood lead level (BLL) was defined as ≥3.5 μg/dL. Of 130 children enrolled in the study, 32 (24.6%) had elevated BLLs. The mean BLL was 3.01 ± 1.14 μg/dL. Multivariate analysis showed that male students (OR=4.47, 95%CI = 1.44–13.85, p = 0.009), who had mothers with lower education (OR=3.85, 95%CI = 1.35–10.95, p = 0.011), and who lived in a house with corrugated iron roofs (OR=8.77, 95%CI = 1.03–74.81, p = 0.047) were more likely to have elevated BLLs than their counterparts. Age, lower socioeconomic status (welfare recipients), water sources at home, fathers smoking, and whether living in urban or rural areas were not found to be associated with elevated BLLs. In conclusion, this study provides preliminary evidence of elevated BLLs in children living in a non-industrial city, like Banda Aceh, and identifies the potential source of domestic exposure to lead. Further study with a larger sample is required to confirm the findings. There is a need to review the current environmental health and waste management policies in Banda Aceh and develop preventive measures.